2012
DOI: 10.1111/anae.12075
|View full text |Cite
|
Sign up to set email alerts
|

The McGrath® Series 5 videolaryngoscope vs the Macintosh laryngoscope: a randomised, controlled trial in patients with a simulated difficult airway

Abstract: Summary We compared the McGrath® Series 5 videolaryngoscope with the Macintosh laryngoscope in a simulated difficult airway, using manual in‐line stabilisation in 88 anaesthestised patients of ASA physical status 1‐2. The primary outcome was laryngoscopic view. Secondary outcomes included rates of successful tracheal intubation and complications. A Cormack and Lehane grade‐1 or ‐2 view was found in all patients when using the McGrath compared with 45 (51%, p < 0.0001) using the Macintosh laryngoscopes. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 32 publications
7
83
4
1
Order By: Relevance
“…It has been reported that the McGrath Series 5 video laryngoscope could not always reduce the TTI even when a clear view of the glottis was achieved. 3 For the McG, the visual field direction and laryngeal axis are not aligned (Fig. 3C).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been reported that the McGrath Series 5 video laryngoscope could not always reduce the TTI even when a clear view of the glottis was achieved. 3 For the McG, the visual field direction and laryngeal axis are not aligned (Fig. 3C).…”
Section: Discussionmentioning
confidence: 97%
“…The angle of the McG blade relative to the axis of the trachea improves the view of the glottis on the monitor; however, it is necessary to redirect the endotracheal tube more anteriorly, and doing so can make it difficult to successfully achieve tracheal intubation. 3 In order to advance the endotracheal tube into the trachea, it is necessary to bend the styletted endotracheal tube to a greater degree than with the MCL. As a result, the TTIs were prolonged in spite of the higher SRs of the intubations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study revealed an intubation time of 47. among studies (6,9,12). While conducting an orotracheal intubation with the McGrath video laryngoscope, a stylet has to be used for the orotracheal tube.…”
Section: Discussionmentioning
confidence: 99%
“…There are several video laryngoscopes in clinical use; however, only limited comparative studies have been conducted to evaluate the exact performance of these devices (5)(6)(7)(8)(9)(11)(12)(13)(14)(15)(16)(17). Hence, we compared the McGrath Series 5 video laryngoscope and the Macintosh laryngoscope in patients who underwent cesarean section.…”
Section: Introductionmentioning
confidence: 99%